Cocoa and Chocolate, Antioxidant Actions and Neuro-Psycho-Emotional Protective Actions, a Short Review - Jurcău, Ramona-Niculina; Jurcău, Ioana-Marieta; Colceriu, Nicolae-Alexandru; Kwak, Dong Hun (Didactica Danubiensis, 2023)
Cocoa and chocolate is a subject of interest in daily lives of many people, but especially in recent years, and research topic due to their beneficial effects already proven on health. The aim of this paper is to present some information on cocoa and chocolate from the perspective of some of their antioxidant and neuro-psycho-emotional actions. The method is based on the structure of a mini narrative review. Cocoa and chocolate have been recognized as a rich source of flavonoids, mainly flavones, important for the beneficial effects on the body. Cocoa has also been found to have effects on the oxidative stress, lipidis, carbohydrates, neurocognition, mood, and behavior. Cocoa and chocolate have multiple beneficial effects, among them, the antioxidant, metabolic and neuro-psycho-emotional ones are very important.